Kondisi Sosial Ekonomi Penduduk Yang Bekerja Di Objek Wisata Alam Bukit Pangonan Tahun 2019 - Trianingrum, Ade Shinta; Sugiyanta, I Gede; Suwarni, Nani (Universitas Lampung, 2021)
This research aims to examine the socio-economic situation of patriarch who works in the pangonan hill natural tourism. This research uses descriptive method. The result of this research indicate that: 1) The education level of patriarch as many as 14 people (elementary school/middle high school), 7 people senior high school graduate, 1 person is college graduate. 2) The natural tourism object of pangonan hill has provided as many as 22 job oppertunitties. 3) Work hours of patriarch as many as 21 people have high rate working hours and 1 people have low rate working hours. 4) The income of the patriarch is 4 people above the average and 18 people below the average. 5) The number of dependents of patriarch that have small category is 17 people, large category is 5 people. 6) The proverty level of patriarch shows that 20 people are on not poor category, 1 person is on poor category, 1 person is on very poor category.Penelitian ini bertujuan untuk mengkaji keadaan sosial ekonomi kepala keluarga yang bekerja di Objek Wisata Alam Bukit Pangonan. Penelitian ini menggunakan metode deskriptif. Hasil penelitian ini menunjukan bahwa (1) Tingkat pendidikan kepala keluarga sebanyak 14 orang (SD/SMP), 7 orang (SMA/SMK), 1 orang (PT). (2) Objek Wisata Alam Bukit Pangonan telah memberikan kesempatan kerja sebanyak 22 orang. (3) Jam kerja kepala keluarga sebanyak 21 orang memiliki jam kerja tinggi dan 1 orang memiliki jam kerja rendah. (4) Pendapatan kepala keluarga sebanyak 4 orang di atas UMK dan 18 orang di bawah UMK. (5) Jumlah tanggungan kepala keluarga yang memiliki kategori kecil sebanyak 17 orang, kategori besar sebanyak 5 orang. (6) Tingkat kemiskinan kepala keluarga yang memiliki kategori tidak miskin sebanyak 20 orang, kategori miskin sebanyak 1 orang, kategori miskin sekali sebanyak 1 orang.Kata kunci : sosial, ekonomi, kepala keluarga.